Exploring EFL Students' Perception on the use of TikTok in Vocabulary Learning beyond the Classroom - Fitriani, Marsha Kurnia; Masykuroh, Qanitah (Universitas Muhammadiyah Surakarta, 2023)
Purpose: The aim of the study is to explore EFL Students’ Perception on The Use of TikTok in Vocabulary Learning beyond the Classroom. Methodology: The study incorporates two types of data: information regarding the use of TikTok and perceptions of TikTok. Data were collected from second-grade students at a state senior high school in Tempuling through questionnaires and interviews. The questionnaire, distributed via Google Forms, comprised sixteen statements prompting student responses. The questionnaire findings were corroborated through interviews with selected students serving as representatives. Data analysis followed the steps outlined by Miles and Huberman (1994) and was thematically analysed to address the research questions. Results: All students possess a TikTok account and utilise the platform to enhance their English vocabulary. Furthermore, students find learning English vocabulary through TikTok to be both facile and enjoyable. Additionally, they derive considerable benefits from employing TikTok for such learning and express a desire for their teachers to utilise the platform for English instruction in the classroom. Applications/Originality/Value: While prior studies primarily examine TikTok's use for learning English within the classroom, this study highlights the use of the platform beyond the classroom and found that learning English vocabularies independently with the help of Tiktok beneficial for students and possible to be complementary to the classroom classical learning.